PENATAAN KAWASAN PARIWISATA AIR TERJUN HUMOGO - Ivo Era-Era Zalukhu; Irwan Wipranata (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
The Humogo Waterfall Tourism Area is one of the waterfall tours located on Nias Island, Fadoro Village, Gunungsitoli Idanoi Subdistrict, Gunungsitoli City, North Sumatra Province. The plan for structuring the Humogo Waterfall Tourism Area is planned based on the Regional Work Plan of the Gunungsitoli City Tourism and Culture Office in 2018, where the arrangement is aimed at adding facilities and infrastructure to support tourism in the Humogo Waterfall Tourism Area and the preparation of the Humogo Waterfall Tourism Area Master Plan, Gunungsitoli city. The Humogo Waterfall area is located in Fadoro Village with an area of 15.5 ha with most of the area still dominated by forests and plantations. The Humogo Waterfall Tourism Area is one of the leading tourist destinations in Gunungsitoli City, which was only opened to the public at the end of 2018. This waterfall has a distinctive characteristic of a multilevel waterfall so it is very interesting to be explored by tourists and has very natural conditions that are still very natural surrounded by trees such as coconut trees, rubber trees and so on. However, this tourism area still has shortcomings in the form of supporting tourism facilities and infrastructure so it is necessary to propose facilities and infrastructure in order to increase the tourist attraction of Humogo Waterfall. The analysis carried out is a policy analysis, site and site analysis, best practice analysis, tourist attraction analysis, perceptions and preferences analysis and analysis of spatial requirements so as to produce proposals and the Humogo Waterfall Tourism Area Planning Plan which is laid out with the concept of ecotourism Keywords: ecotourism; nature tourism; tourist zoning; waterfall tourism region AbstrakKawasan Pariwisata Air Terjun Humogo merupakan salah salah satu wisata air terjun yang terletak di Pulau Nias, tepatnya di Desa Fadoro, Kecamatan Gunungsitoli Idanoi, Kota Gunungsitoli, Provinsi Sumatera Utara. Rencana penataan Kawasan Pariwisata Air Terjun Humogo direncanakan berdasarkan Rencana Kerja Perangkat Daerah Dinas Pariwisata dan Kebudayaan Kota Gunungsitoli Tahun 2018, dimana penataan yang dilakukan bertujuan untuk menambah fasilitas dan prasarana yang mendukung pariwisata di Kawasan Pariwisata Air Terjun Humogo dan penyusunan Masterplan Kawasan Pariwisata Air Terjun Humogo, Kota Gunungsitoli. Kawasan Air Terjun Humogo terletak di Desa Fadoro dengan luas 15,5 ha dengan sebagian besar kawasan masih didominasi oleh hutan dan perkebunan. Kawasan Pariwisata Air Terjun Humogo merupakan salah satu destinasi wisata unggulan di Kota Gunungsitoli yang baru dibuka untuk umum pada akhir tahun 2018. Air terjun ini memiliki ciri khas yaitu air terjun yang bertingkat sehingga sangat menarik untuk dijelajahi oleh wisatawan serta memiliki kondisi alam yang masih sangat alami yang dikelilingi oleh pepohonan seperti pohon kelapa, pohon karet dan lain sebagainya. Namun area wisata ini masih memiliki kekurangan berupa sarana dan prasarana penunjang wisata sehingga diperlukan usulan fasilitas dan prasarana agar dapat meningkatkan daya tarik wisata Air Terjun Humogo. Analisis yang dilakukan adalah analisis kebijakan, analisis lokasi dan tapak, analisis best practice, analisis daya tarik wisata, analisis persepsi dan preferensi serta analisis kebutuhan ruang sehingga menghasilkan usulan dan Rencana Penataan Kawasan Pariwisata Air Terjun Humogo yang ditata dengan konsep ekowisata.